Central nervous system inflammatory demyelinating diseases and neuroimmunology in Singapore—Epidemiology and evolution of an emerging subspecialty. Issue 4 (19th January 2021) - Tan, Kevin; Yeo, Tianrong; Yong, Kok Pin; Thomas, Terrence; Wang, Furene; Tye, Janis; Quek, Amy May Lin
Abstract: The clinico‐pathologic entity of central nervous system inflammatory demyelinating diseases (CNS IDD) such as multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD) was recognized in Singapore as early as the 1960s but were previously under‐diagnosed and under‐researched. Access to neuroimmunology expertise, advanced neuroimaging and novel neural antibody biomarkers that distinguish aquaporin‐4 antibody‐positive NMOSD (AQP4 NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD) from MS have revolutionized the clinical management of patients with CNS IDD in Singapore. Based on pooled cross‐sectional data from government‐funded hospitals in 2020, we identified 468 CNS IDD patients (265 MS, 152 AQP4 NMOSD, and 51 MOGAD) in Singapore. Based on a population size of approximately 4 million, the crude prevalence estimates of MS are 6.6 per 100 000, AQP4 NMOSD 3.8 per 100 000, and MOGAD 1.3 per 100 000. There are marked differences in MS and AQP4 NMOSD prevalence between ethnic groups; MS prevalence is highest in Eurasian (mixed Caucasian‐Asian ancestry) (23.9 per 100 000), followed by Indian (17.5 per 100 000), Malay (9.2 per 100 000), and Chinese (4 per 100 000); AQP4 NMOSD prevalence is highest in Chinese (4.5 per 100 000), followed by Eurasian (3.9 per 100 000), Malay (1.5 per 100 000), and Indian (1.1 per 100 000). The past decade has seen remarkable growth in neuroimmunology in Singapore. We aim to foster the development of interdisciplinary care, clinical, translational, and health services research that impact local healthcare policies and research priorities, and patient support groups to better navigate through this rapidly evolving landscape.